Skema Proteksi Hak Cipta untuk Citra Warna Digital Menggunakan Visual Cryptography - Septia Rani; Agus Harjoko (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Currently, cases of misuse of intellectual property such as digital image have occurred frequently. Copyright protection needs to be done to reduce the occurrence of cases of misuse of a digital image by an unauthorized person. Watermark image can be used to mark the ownership of a digital image. In this paper, a copyright protection scheme based on visual cryptography for digital color image is proposed. Visual cryptography is chosen because it is easy to implement and has a high level of security. Unlike most conventional watermarking schemes, the image to be protected is not directly modified by embedding the watermark into it. Visual cryptography technique is used to generate two share images, namely ownership share image and master share image. To identify the ownership of the image, the watermark can be obtained by stacking the master share image with the ownership share image. Some experiments are carried out to assess the robustness and security performance of the proposed scheme. The results show that the proposed scheme meets the security criteria and has shown robustness against image processing attacks, demonstrated by the acquisition of the average value of the extracted watermark accuracy ratio that is equal to 0.94537.